2012
DOI: 10.4236/fns.2012.311205
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Combined Effects of Nucleotides and Human Milk Oligosaccharides on Proliferation, Apoptosis and Necrosis in a Human Fetal Intestinal Cell Line

Abstract: Nucleotides (NT) and human milk oligosaccharides (HMO) individually affect epithelial cell growth, but their combined effects had not been studied. Herein, the impact of NT and HMO on cell proliferation, apoptosis, necrosis and cell cycle in the fetal epithelial cell line (FHs-74 Int) was determined. Cells were incubated with media containing 2.5% FBS and no epidermal growth factor (Control); fucosyllactose (FL) mix [85% 2'FL/15% 3'FL], sialyllactose (SL) mix [40% 6'SL/10% 3'SL/50% sialic acid (SA)] or LNnT at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A previous study by Kuntz et al [ 57 ] reported that proliferation rates of HT29 and Caco-2 cells was inhibited by neutral oligosaccharides (2.3 and 0.2 mg/mL respectively) and acidic oligosaccharide (0.3 and 0.7 mg/mL respectively) isolated from human milk [ 57 ]. In contrast, 1 mg/mL lactose had no effect on the proliferation of primary human foetal intestinal cells [ 58 ], but proliferation of the same cell line was increased after exposure to whey produced from bovine colostrum [ 59 ] and complete human milk [ 60 ]. Thus, it could be suggested that treatment of IECs with purified preparations of neutral or acidic oligosaccharides inhibits cellular proliferation to a greater extent than IECs exposed to treatments comprised of a combination of carbohydrates such as the CF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Kuntz et al [ 57 ] reported that proliferation rates of HT29 and Caco-2 cells was inhibited by neutral oligosaccharides (2.3 and 0.2 mg/mL respectively) and acidic oligosaccharide (0.3 and 0.7 mg/mL respectively) isolated from human milk [ 57 ]. In contrast, 1 mg/mL lactose had no effect on the proliferation of primary human foetal intestinal cells [ 58 ], but proliferation of the same cell line was increased after exposure to whey produced from bovine colostrum [ 59 ] and complete human milk [ 60 ]. Thus, it could be suggested that treatment of IECs with purified preparations of neutral or acidic oligosaccharides inhibits cellular proliferation to a greater extent than IECs exposed to treatments comprised of a combination of carbohydrates such as the CF.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it could be suggested that treatment of IECs with purified preparations of neutral or acidic oligosaccharides inhibits cellular proliferation to a greater extent than IECs exposed to treatments comprised of a combination of carbohydrates such as the CF. How this relates to the mechanism of action was not determined in this study, but it is known that neutral and acidic oligosaccharides inhibit proliferation rates of IECs through alterations in epidermal growth factor receptor (EGFR) signalling and cell cycle regulators [ 58 , 61 ], and human milk increases proliferation through a unique tyrosine kinase pathway [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, proliferation rates of pre-confluent HT29 cell cultures were reduced after incubation with neutral and acidic oligosaccharides (0.2 and 0.4 mg/mL respectively) from human milk, although Caco-2 brush border-expressing cultures were unaffected at these concentrations [ 77 ]. However, proliferation of primary human foetal intestinal cells when incubated (72 h) with 1 mg/mL lactose and tri-galactose was unchanged [ 78 ]. In contrast, proliferation of the same cell line, was increased after 48 h exposure to whey produced from bovine colostrum at concentrations ranging from 0.3% to 10% v / v [ 79 ] and also complete human milk at concentrations ranging from 1% to 10% v / v after 24 h exposure [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it could be hypothesised that neutral or acidic oligosaccharides, as purified preparations, are able to elicit a greater response in inhibiting cellular proliferation than samples comprised of combinations of acidic and neutral oligosaccharides in conjunction with other saccharides components. Whether this could also be related to their mechanism of action requires further study; previous reports indicate that neutral and acidic oligosaccharides induce growth inhibition in intestinal epithelial cell cultures through changes in EGFR signalling and gene expression of cell cycle regulators [ 59 , 78 ]. In contrast, complete human milk increases cell proliferation but not through the EGFR signalling but via a unique tyrosine kinase pathway [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both 2′-FL ( P = 0·07) and the combination of fucosylated HMO (FL mix; P = 0·10) tended to inhibit proliferation. Whether HMO affect immune cell proliferation through the regulation of cyclin expression, as has been demonstrated in epithelial cells ( 34 , 42 ) , or through a more novel mechanism, such as fucose modification of Notch receptors or ligands ( 43 ) , is unknown and should be tested. In terms of cytokine production, stimulation of PBMC with iHMO doubled IL-10 production by PBMC.…”
Section: Discussionmentioning
confidence: 99%